0906 Chronotypes in comorbid Insomnia and Alcohol Use Disorder. (12th April 2019) - Taylor, Brittany; He, Sean; Thakur, Nina; Chakravorty, Subhajit
Abstract: Introduction: Insomnia is by far the most prevalent sleep disorder in patients with Alcohol Use Disorder (AUD) and persisting insomnia during recovery increases their risk of relapse. Emerging data from adolescents and adults has demonstrated that an evening chronotype is linked to drinking and psychiatric disorders. In contrast, very little is known about chronotypes in AUD comorbid with insomnia. Methods: A cross-sectional study of baseline data from a treatment study. The following rating scales assessed the relevant clinical domains: Composite Scale of Morningness (CSM, for chronotypes), Insomnia Severity Index (ISI, insomnia) and sleep diaries (insomnia symptoms), Time Line Follow Back interview (alcohol consumption in the last 90 days), Penn Alcohol Craving Scale (PACS, alcohol craving in the last 7 days), Short Index of Problems (SIP, psychosocial problems from the drinking), Beck Depression Inventory-II (depressive symptoms), with GAD-7 (anxiety symptoms) and Columbia-Suicide Severity Rating Scale (suicidal behavior). The ISI was evaluated as the total score, insomnia symptoms (Q1a-1c) and insomnia ramifications (Q2-5). Linear regression analyses evaluated the association between individual clinical scales (outcomes) and CSM total score (predictor). Results: The mean CSM total score was 36.6(SD=6.5); they included, morning type (N=9), evening type(N=1) and intermediate(N=47). Their mean ISI total score was 19.4 (SD=3.4) and they consumed 8.9 (SD=8.2) alcoholic drinks per day over the last 90 days. The CSM total score demonstrated inverse relationships with ISI total score (β=-0.2; t=-3.0; 95%C.I.=-0.3, -0.07), ISI symptoms (β=-0.06; t=-2.0; 95%C.I.=-0.1, -0.0009), ISI daytime ramifications (β=-0.1; t=-3.0; 95%C.I.=-0.2, -0.04), sleep onset latency (β=-1.8; t=-2.5; 95%C.I.=-3.3, -0.3). Furthermore, CSM total score was linked to time spent thinking about alcohol (β=-0.06; t=-2.05; 95%C.I.=-0.1, -0.001) and a nonsignificant trend for an association with overall alcohol craving (β=-0.05; t=-1.7; 95%C.I.=-0.1, 0.008). The CSM total score was not associated with sleep duration, drinks per day or with the total scores of BDI, GAD-7, PACS, SIP and CSSRS, although linear trends were seen for increased scores from morning to evening chronotypes. Conclusion: The predominant chronotype in treatment-seeking AUD patients with insomnia was an intermediate chronotype. Morning-type individuals had lower severity of comorbid complaints. Support (If Any): VA grant IK2CX000855(S.C.)